Functional dyspepsia: outcome of focus groups for the development of a questionnaire for symptom assessment in patients suffering from postprandial distress syndrome (PDS). Issue 9 (29th July 2014) - Carbone, F.; Holvoet, L.; Vandenberghe, A.; Tack, J.
Abstract Background To date, no patient reported outcomes (PRO) instrument is available for evaluation of treatment efficacy in functional dyspepsia (FD)/postprandial distress syndrome (PDS). The aim of our study was to perform focus group interviews for the development of a new questionnaire for assessing symptom pattern and severity in PDS. Methods Random ambulatory patients diagnosed with FD/PDS based on Rome III criteria and no predominant gastro‐esophageal reflux disease (GERD) symptoms were invited to participate. Focus group sessions were organized where patients reported and discussed their symptoms, facilitated by an experienced physician. After reaching saturation of identified symptom items, questions for a pilot PRO instrument were drafted and evaluated in cognitive interviews for relevance, clarity, and consistency. Key Results Of 225 screened patients, 26 patients were diagnosed with PDS without overlapping GERD as single final diagnosis. Fifteen of these (87% female, 48 ± 3.2 years) participated in one of three focus groups. All (100%) confirmed experiencing symptoms that were triggered or aggravated by ingestion of a meal, corresponding to early satiation (100%), and postprandial fullness (100%). In addition reported gastroduodenal symptoms were nausea (40%, postprandial in all, interprandial in 20%), upper abdominal bloating (33%), excessive belching (27%), and vomiting (13%). Epigastric pain and burning were present in respectively 20% and 13%. Non‐gastroduodenal symptoms that patients reported included heartburn (33%, but mostly sporadic), weight loss (93%, on average 5.0 ± 1.7 kg), and fatigue (67%). Questions evaluating these symptoms were validated in 15 cognitive interviews. Conclusions & Inferences This focus group study confirms symptoms corresponding to postprandial fullness and early satiation as the key items for developing a PRO for PDS.